Effects of Chromium Doping on the Electrical Properties of ZnO Nanoparticles - S. Janet Priscilla; V. Andria Judi; R. Daniel; K. Sivaji (Ital Publication, 2020)
Nanostructured ZnO has gained a considerable amount of attention due to its unique physical and chemical properties and due to its remarkable performance in the fields of optics, photonics and electronics. The scope of this work is to study the Structural, Optical and Electronic properties of Pure Zinc Oxide (ZnO) and Chromium doped Zinc Oxide nanoparticles. These nanoparticles were synthesized by low-temperature precipitation method at various concentrations in the range (Zn1-xCrxO; (x = 0, 0.1& 0.3)). The precursors used were analytical grade Zinc Nitrate Hexahydrate and Chromium Nitrate Nona hydrate. The synthesized nanoparticles were annealed at 400°C. The Structural property of the synthesized nanoparticles was analysed by XRD (X-Ray diffraction) and was confirmed to exhibit a crystalline hexagonal wurtzite structure with an average crystallite size of 55nm. The functional groups were analysed using FTIR (Fourier Transformed Infra-red spectroscopy). The Morphology was analysed by FESEM (Field Emission Scanning Electron Microscope) and a change in morphology from spherical to spindle like structure was observed. The Optical properties were analysed using UV-Vis spectroscopy, the absorption spectrum for electromagnetic spectrum was observed and the changes in the optical band gap of ZnO nanoparticles with Chromium dopant addition were calculated to be in the range of 3.6 eV. The Electrical property of the synthesised nanoparticles was analysed using Electrochemical Impedance Spectroscopy (EIS) and the conductivity was calculated to be in the range of 1.1e-07S/m.